PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP NILAI PERUSAHAAN - Resmiati, Deder (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is meant to examine the mechanism influence of Good Corporate Governance (GCG) and Corporate Social Responsibility Disclosure to the companyâs value. The companyâs value in this research isproxy by Tobinâs Q value. The result of F-test indicates that the board of commissioners, managementownerships, public ownerships and Corporate Social Responsibility Disclosure altogether has an influence to thecompany value. It means the companies which apply CSR and GCG will turn up the trust of investors so it willbe responded positively through the improvement of the companys share price. The result of this researchindicates that the t-test of the board of commissioners, public ownerships, management ownerships partiallyhave no influence to the companyâs value while the CSR disclosure has an influence to the companyâs value. Theboard of commissioners has no influence to the companyâs value since the board of commissioners is occasionallytend to do intervention to the management. Public ownerships partially have no influence to the company valuesince the number of public ownerships are large and scattered thus they cannot be united and mostly are notrepresented in making decision so they have no influence to the companyâs value. Management ownerships haveno influence to the companyâs value since the management stock ownerships is low it causes the managementperformance has not work maximally yet so the management ownerships cannot become a mechanism to improvethe companyâs value. While, the CSR Disclosure has an influence to the companyâs value since the presence ofthe CSR Disclosure is conducted by the company therefore investors will respond positively through theimprovement of share price so it will raise the companyâs value. Keywords:Â  Company Value, Board of Commissioners, Public Ownerships, Management Ownerships andCorporate Social Responsibility Disclosure.